Kontribusi Tingkat Pendidikan Orang Tua Dan Motivasi Berprestasi Terhadap Kedisiplinan Dan Dampaknya Pada Prestasi Belajar Fisika Pada Siswa Kelas X Sman 1 Sambungmacan Tahun Pelajaran 2015/2016 - Sutarjo, Sutarjo, Dr. Sumardi, M.Si, Dr. Sabar Narimo, M.M, M.Pd (2016)
ABSTRACT SUTARJO , Q100140023 . CONTRIBUTION TO EDUCATION LEVEL OF PARENTS AND ACHIEVEMENT MOTIVATION OF DISCIPLINE AND ITS IMPACT ON THE ACHIEVEMENT OF PHYSICS IN CLASS X SMAN 1 SAMBUNGMACAN YEAR STUDY 2015/2016 . THESIS. MUHAMMADIYAH SURAKARTA UNIVERSITY. 2016. This study aims to (1) examine the contribution level of parents 'education and achievement motivation on learning achievement physics indirectly through discipline, (2) examine the contribution level of parents' education and achievement motivation on discipline, (3) examine the contribution of the discipline of learning achievement physics. This research is a quantitative research. The study population was all students of class X at SMAN 1 Sambungmacan the academic year 2015/2016, amounting to 166. The sample in this study were 117 students by using proportional random sampling technique. Data collection techniques used are questionnaires and tests. All the variables have fulfilled the prerequisite test. Data analysis technique used is path analysis (path analysis). From the results of data analysis can be concluded (1) the contribution level of parents' education and achievement motivation on learning achievement physics indirectly through discipline generate indirect effect (IE), each for 0.924 or 0.804 or 9.24% and 8.04%, and the magnitude of the effective contribution of the three variables to achievement learn physics by 75.8% , (2) there is contribution level of parents' education and achievement motivation simultaneously to discipline F> F table at 84.229 with a probability value (sig) = 0,000 ˂ 0.05. The value of the effective contribution of 59.1%, (3) there is contribution to the discipline of learning physics learning achievement by producing a direct effect (DE) by 4% and the effective contribution of 14.88% with a significance level of = 0.05 and p = 0.007. Keywords: discipline, achievement motivation, student achievement, parental education